Production and quality of banana ‘BRS Conquista’ bagged with different colored polypropylene bags - Martins, Rafaelly Calsavara; Souza, Jackson Mirellys Azevêdo; Silva, Marcelo de Souza; Parreiras, Nathália de Souza; Silva, Marcela Sant'Anna Cordeiro da; Bolfarini, Ana Carolina Batista; Ferreira, Rafael Bibiano; Leonel, Sarita (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Worldwide, the second most traded fruit is banana, which is highly appreciated by Brazilian consumers. Moreover, new technologies have been used to improve fruit quality during cultivation. This study aimed to assess the influence of plastic bag colors on the production and quality of banana ‘BRS Conquista’. The treatments consisted of the use of commercial polypropylene bags e colored white, black, red or blue, in addition to the control (non-bagged). This study used a randomized complete block design with five treatments, four replicates and four plants per plot, totalling 80 plants. The assessments consisted of bunch mass; rachis mass; fruit total mass; mean cluster mass; number of fruits per bunch and per cluster; and fruit length and diameter; along with fruits physicochemical traits, such as soluble solids, titratable acidity, pulp/peel ratio and maturation index. The results indicated that no interference was obtained from the different plastic bag colors in the productive variables. However, a greater content of soluble solids was observed in the non-bagged bunches.